Airport Exposure to Lightning Strike Hazard in the Contiguous United States. Issue 8 (10th November 2020) - He, Yiyi; Lindbergh, Sarah; Graves, Coolidge; Rakas, Jasenka
Abstract: Reliability of the air transportation system heavily depends on the performance of communication, navigation, and surveillance facilities in the National Airspace System (NAS). These facilities are prone to outages caused by convective weather, such as lightning. Current lightning safety standards and risk assessments focus solely on lightning occurrence and omit the effect of lightning intensity from hazard characterization. We propose methods that incorporate lightning intensity and occurrence parameters to better understand the impact of lightning strike on the NAS using the National Lightning Detection Network and Federal Aviation Administration NAS facilities and equipment outage databases. Spatial analysis and clustering reveal different exposure profiles for 436 U.S. airports. Kernel Density estimation and Hot Spot analysis show that regardless of lightning intensity, Southern state airports are the most exposed to lightning hazards. K ‐means clustering reveal five different lightning exposure profiles that mimic the spatial patterns produced by the Kernel Density estimation and Hot Spot analysis. A scoring system ranks all airports according to their exposure profile taking into consideration lightning occurrence and intensity. It is complemented with a rising trend exposure analysis, which identifies airports whose exposure could be underestimated under the current standards, identifying airports with fewer lightning occurrences but higher intensities. Finally, a comparison between the exposure patterns and lightning‐induced outages provide insights into U.S. lightning impact patterns. Similar patterns between lightning exposure and outages indicate that the results of the proposed lightning hazard assessment provide useful information for prioritizing airport hardening investments at the national scale and reducing lightning risk.